Tourism promotion and urban space in Barcelona: historic perspective and critical review, 1900-1936 - Cocola-Gant, Agustín (2017)
This paper focuses on the historic connections between tourist promotion as a factor for both capital attraction and competitiveness and its influence on the urban configuration of Barcelona. Today, tourism represents a strategic value in the urban organisation of Barcelona and constitutes an excuse for the design, management and planning of the city, but the genealogy of this process has not been considered. In analysing this origin, the paper emphasises the validity of the strategies that were used at the beginning of the 20th century and makes a parallelism with the current promotion of the city. The tourist construction of Barcelona originated in the framework of the bourgeois ideology, which placed aesthetic and cultural values as a core idea of its discourse. Both the urban reconfiguration and the monumental construction of Barcelona were a prerequisite and a consequence of this promotion.